An Assistance Processing Waste into Crafts to Increase the Creativity of TPQ Al Ikhlas Students at Tanjung Harapan Village - M. Aali Mustahfidzil M; Reno Tegar Pangestu; Malik Abdul Aziz; Refi Fadilah Oktavia; Habibi Fajri; Febri Ilham Nurcholis; Firman Adi Adam; Rafiqha Mufti; Rela Amalia; Nurliza Masroatul M; Siti Logaya; Yunita Sari; Isnaini Nur Azizah (International Journal of Community Engagement Payungi, 2024)
The service activity of UMALA Metro lecturers and students in Tanjung Harapan Village is "Internalization of Ahlusunnah Wal Jama'ah Values in Forming Community Character and Empowering Creative Economy Based on Local Potential", while producing work that will be useful and memorable for the community in Tanjung Harapan Village, Seputih Banyak District. The aim of this activity is to provide an alternative to the waste problem that exists in society, especially inorganic waste so that it has economic value and usefulness, as well as to increase the creativity of children in the village, especially students at TPQ Al Ikhlas in making handicrafts from water bottle caps. mineral. The community service program carried out is intended to reduce waste scattered everywhere, which is then processed into handicrafts. Method: PAR (Participatory Action Research), namely service based on problems that are discovered and then provide alternative solutions. Results: The use of this waste makes a craft to increase creativity for students at TPQ Al Ikhlas, using the recycling method to produce a work of artistic and economic value. Conclusion: The introduction of the PAR method using the 5T method (To Know, To Understand, To Plan, To Action, To Reflection) to find alternative solutions to a waste problem makes crafting a form of student creativity